NALISIS GAYA KEPEMIMPINAN, MOTIVASI KERJA, STRES KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA KANTOR KESATUAN BANGSA DAN POLITIK LABUHANBATU - Syafitri ,; Novrihan Leily Nasution; Aulia Indra (JOURNAL ECONOMICS AND STRATEGY, 2021)
This study was conducted to prove whether the results with the same previous research would have obtained similar results or not if the research location was carried out at the Labuhanbatu National and Political Unity office. This study was conducted using 30 samples which were analyzed by multiple linear regression. The primary data used in the study were collected by distributing questionnaires. From the data collected, it was processed using SPPS version 23. The result is that leadership style and compensation do not have a positive and significant effect on performance, work motivation and work stress have a positive and significant effect on performance, for the t test while for the F test the four variables studied (Leadership Style, Work Motivation, Job Stress, and Compensation in simultaneous positive and significant effect on employee performance). these four variables are able to explain the performance of 44.4 percent.